Efficient Power Management Strategy and Challenges of Hybrid Renewable Energy Based Electric Vehicles - A Review - Zaman, Md Rakibur; Hoque, Md Reazul; Hussain, Md. Naeem; Ali, Md Shopan (Control Systems and Optimization Letters, 2024)
Forging a new paradigm in the automobile industry, hybrid electric vehicles (HEVs) coupled with renewable energy sources are a result of the increased focus on sustainable transportation. To better understand the difficulties involved in deploying hybrid renewable energy-powered electric vehicles, this article explores effective power management solutions. Power management techniques that are complex are required when integrating renewable energy sources, including solar and wind, with hybrid electric vehicles. Although the use of renewable energy in electric vehicles appears promising, several obstacles prevent widespread use. This study tackles dynamic difficulties such as the requirement for robust energy management systems, the intermittent nature of renewable energy sources, and the limited storage capacity aboard. The paper outlines new technological developments that aim to improve the incorporation of renewable energy sources into electric vehicles as a solution to the issues that have been highlighted. This review addresses the challenges associated with incorporation of renewable energy and electric vehicles.  Addressing the challenges requires collaboration among stakeholders, technological advancements, and supportive policies to foster the widespread adoption of sustainable transportation solutions. The study highlights the effectiveness of various power management systems through case studies that show how hybrid renewable energy-based electric vehicles are used in the real world. The effective power management techniques and difficulties related to hybrid electric vehicles powered by renewable energy sources are thoroughly examined in this research. It adds to the current conversation on sustainable transportation by tackling the ever-changing problems and putting forward creative solutions, which could influence developments that could influence the direction of electric mobility in the future. The optimal utilization of energy provided from renewable sources, such solar panels or wind turbines, is ensured by effective power management. A cleaner and more sustainable transportation system is made possible by an effective power management plan, which maximizes the use of renewable energy. HREVs can benefit from the best grid conditions, electricity costs, and charging periods when they are integrated with smart charging infrastructure.